Transcriptional regulation in skeletal muscle and adipose tissue of lean and obese colony cats - Rahel Rigotti; Annette Liesegang; Holly Dawson; Daniel Brugger; Diana Frey; Georgina Samaha; Bianca Haase; Brigitta Wichert (PLoS ONE, 2026)
This study analysed gene expression profiles in white adipose and skeletal muscle tissues of cats genetically predisposed to obesity and wildtype cats to uncover molecular mechanisms regulating obesity. It also examined how these profiles altered after change in body fat through changes in the amount of food. For this purpose, 3 female cats with phenotype lean (GL) and 3 female cats with phenotype obese (GO) were included in the study. Fat and muscle samples were obtained twice from these cats (T1 = all cats lean, T2 = after ad libitum feeding GL still lean, GO obese). In addition Body Conditions Score (BCS) was measured at both time points, body fat content was determined using DEXA and blood samples were taken to measure glucose levels. BCS revealed a significant positive linear regression with body fat content. Comparing BCS and blood glucose level, no significant difference was observed. The study found distinct gene expression changes in muscle and adipose tissues when comparing obese and lean cats at two time points (T1 and T2). In muscle tissue, group differences between obese and lean cats were detected in three downregulated and four upregulated genes when all cats were lean, while only two genes were upregulated when one group of cats became obese (T2). For adipose tissue, fewer differences were observed, with minimal changes in gene expression between the two groups, especially at T2, where lean cats showed only one downregulated gene and obese cats showed no change. The regulated genes identified are mainly involved in tissue maintenance and cellular turnover, either specific to the tissue studied or with broader roles. No clear phenotypic trend in gene expression was observed. Differences emerged mainly within the obese group over time, reflecting adaptive feeding responses, while tissue-specific differences in the transcriptome were most prominent. Overall, phenotype had no distinct effect on gene expression patterns.